Epigenetic immunomodulatory effect of eugenol and astaxanthin on doxorubicin cytotoxicity in hormonal positive breast Cancer cells - Mariam A. Fouad (BMC Pharmacology and Toxicology, 2021)
Abstract Background Hormonal receptor positive (HR+) breast cancer is the most commonly diagnosed molecular subtype of breast cancer; which showed good response to doxorubicin (DOX)-based chemotherapy. Eugenol (EUG) and astaxanthin (AST) are natural compounds with proved epigenetic and immunomodulatory effects in several cancer cell lines. This study has been initiated to investigate the molecular mechanism (s) whereby EUG and AST could enhance DOX cytotoxicity in MCF7 cells. Methods Cytotoxic activity of DOX alone and combined with either 1 mM EUG or 40 μM AST was performed using sulphorhodamine-B assay in MCF7 cells. Global histones acetylation and some immunological markers were investigated using ELISA, western blotting and quantitative RT-PCR techniques. Functional assay of multidrug resistance was performed using rhodamine 123 and Hoechst 3342 dyes. Flow cytometry with annexin V and propidium iodide were used to assess the change in cell cycle and apoptosis along with the expression of some differentiation, apoptosis and autophagy proteins. Results DOX alone resulted in concentration-dependent cytotoxicity with IC50 of 0.5 μM. Both EUG and AST significantly increased DOX cytotoxicity which is manifested as a significant decrease in DOX IC50 from 0.5 μM to 0.088 μM with EUG and to 0.06 μM with AST. Combinations of DOX with 1 mM EUG or 40 μM AST significantly increased the level of histones acetylation and histone acetyl transferase expression, while reduced the expression of aromatase and epidermal growth factor receptor (EGFR) when compared with 0.25 μM DOX alone. Also both combinations showed higher uptake of rhodamine but lower of Hoechst stains, along with increased the percentage of caspase 3, and decreased the expression of CK7 and LC3BI/II ratio. EUG combination induced IFγ but reduced TNFα causing shifting of cells from G2/M to S and G0/ G1 phases. Combination of DOX with EUG induced apoptosis through the higher BAX/ BCl2 ratio, while with AST was through the increase in caspase 8 expressions. Conclusion EUG and AST potentiated the anticancer activity of DOX through epigenetic histones acetylation along with the immunonomodulation of different apoptotic approaches in MCF7 cells.